Do Managers Learn from Analyst Participation in Conference Calls? - YONG, Amanda Aw Zhi Xin (Institutional Knowledge at Singapore Management University, 2022)
While research finds that conference calls are informative to the market and analysts, they can also be informative to managers as analysts’ questions can provide a feedback effect. Using a sample of conference call transcripts from 2002 to 2018, we find that greater analyst participation, as measured by the number of words spoken by analysts relative to the number of words spoken by managers during conference calls, is associated with higher accuracy in managers’ subsequent earnings forecasts. Cross-sectional tests show that this positive association is more pronounced when managers use more uncertain words in conference calls, when analysts use a more negative tone to question management, and when participating analysts have higher industry expertise. We also employ a topic modeling approach and find that managers are more likely to benefit from conference calls when analysts question management about the company’s revenues, margins, customers, or business outlooks. Overall, our results are consistent with analyst participation in conference calls contributing to managerial learning.